The Link Between Gut Microbiota and Depression: Exploring the Correlation - Juśkiewicz, Adam; Grelewicz, Olga; Kucy, Natalia; Servaas, Elwira; Haber, Mateusz; Kula, Paula; Czachor, Adrianna; Kotula , Alicja (Journal of Education, Health and Sport, 2025)
Introduction: Depression represents a significant global health challenge, affecting approximately 4.4% of the global population and ranking as the leading cause of disability worldwide. Despite advancements in pharmacotherapy and psychotherapeutic interventions, a substantial proportion of individuals with depression experience treatment resistance, recurrence of symptoms, or inadequate response to standard treatments. Aim of the Study: This review explores the emerging role of the gut microbiome in depression, focusing on its potential as a therapeutic target. Materials and Methods: A comprehensive literature search was conducted using electronic databases including PubMed/MEDLINE and Google Scholar. The search encompassed articles utilizing keywords and Medical Subject Headings (MeSH) terms related to “gut microbiome,” “depression,” “microbiota-gut-brain axis,” “psychiatric disorders,” and “clinical studies.” Conclusion: Therapeutic strategies targeting the gut microbiota offer promising avenues for alleviating depressive symptoms and enhancing treatment outcomes. Probiotics, prebiotics, dietary modifications, and fecal microbiota transplantation (FMT) represent diverse interventions aimed at restoring microbial balance, modulating gut-brain communication, and reducing neuroinflammation associated with depression. Further research is needed to optimize therapeutic approaches, explore personalized medicine strategies based on individual microbiome profiles and clarify the safety and efficacy of microbial-based therapies in clinical settings.